Chemical Composition and Quality Changes in Bonga (Ethmalosa fimbriata) Canned in Oil and Tomato Sauce - G.R., Akande; E.O., Faturoti (Fishery Technology, 2025)
Changes in the quality of canned Bonga Ethmalosa fimbriata packed in deodourized vegetable oil and tomato sauce during various stages of processing and storage were examined using some indices of chemical spoilage. Proximate composition, total amino acids and available lysine content were determined for raw, precooked and canned bonga products. No significant differences (p>0.05) in the total amino acids composition was however observed among raw, precooked and canned bonga. There was a decrease in available lysine in the different phases of the process but no loss in total amino acid composition. TBA values gave good correlation of rancidity development with storage time. TMA and TVN levels were affected by precooking and thermal treatment and were found not to be useful as post canning indicators of quality.